PENENTUAN TINGKAT PENGGUNAAN MINERAL ORGANIK UNTUK MEMPERBAIKI BIOPROSES RUMEN PADA KAMBING SECARA IN VITRO - Muhtarudin Muhtarudin; Liman Liman (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
The objective of research was to determine utilization level of organic mineral both macro (Ca, Mg) and micro (Zn, Cu, Cr, Se) mineral by in vitro method. The research had two steps, the first, determine utilization level of micro organic mineral.The research used completely randomized design with 5 treatments and 6 replications. The treatments were arranged i.e: basic rations (30% forage+70% concentrate); basic rations +0.5 times recomendation of organic micro mineral, basic rations + 1 times recomendation of organic micro mineral, basic rations + 1.5 times recomendation of organic micro mineral, and basic rations+2 times recomendation of organic micro mineral. Secondly, the research had done to determine utilization level of macro organic mineral. The research used completely randomized design with 5 treatments and 6 replications The treatments were arranged i.e: basic rations (30% forage + 70% concentrate); basic rations +0.5 times recomendation of organic macro mineral, basic rations+1 times recomendation of organic macro mineral, basic rations +1.5 times recomendation of organic macro mineral, and basic rations+2 times recomendation of organic macro mineral. The parameters consisted i.e: containing of volatil fatty acid, ammonia, dry matter digestibility, and organic matter digestibility. The result showed (1) based on dry matter digestibility, and organic matter digestibility, the best level of utilization of organic macro mineral was 1 times recomendation of NRC (1985) based on organic matter digestibility, the best level of utilization of organic micro mineral was 1.5 times recomendation of NRC.